Purple rain [videorecording (Blu-Ray)] - Magnoli, Albert; Blinn, William; Prince; Prince; Prince; Apollonia; Day, Morris; Karlatos, Olga; Williams, Clarence, III, 1939-2021; Thorin, Donald E.; Colombier, Michel (Warner Bros. Entertainment, 2016)
Prince stars as "The Kid," a Minneapolis club musician, who struggles with both a tumultous homelife and his own smoldering anger while taking refuge in his music and his steamy love for sultry Apollonia Kotero. Semi-autobiographical